Molecular design, synthesis and biomedical applications of stimuli-responsive shape memory hydrogels. (May 2019) - Liang, Ruixue; Wang, Li; Yu, Haojie; Khan, Amin; Ul Amin, Bilal; Khan, Rizwan Ullah
Graphical abstract: Abstract: The review article encompasses an overview of the contemporary research related to an arsenal of smart materials i.e., shape memory hydrogels (SMHs). SMHs are instrumental in fixing temporary shapes or recovering permanent ones in response to external stimuli and are playing an increasingly important role in a diverse range of applications including soft robots, artificial mussels, embolic agents and so forth. As cynosure of smart materials, SMHs have attracted considerable attention in recent years owing to their unique functionality. We highlighted the mechanism of the shape memory effect (SME) and the design principle of SMHs coupled with recent advances in four distinct classes of SMHs where SME is triggered in response to temperature, pH, chemicals, and light. Besides, the progress in biomedical applications of SMHs has also been presented.